Engineering immunomodulatory biomaterials to combat bacterial infections - Gomez Casas, Carolina; Shukla, Anita (Frontiers in Biomaterials Science, 2024)
Modulating the immune system using engineered materials is an emerging strategy to combat bacterial infections. Bacteria adopt immune evasion strategies to ensure their survival, ultimately leading to persistence and recurrence of infections. With a rise in antimicrobial resistance and a decrease in antibiotic efficacy, host-directed therapies using immunomodulatory biomaterials are a promising approach to infection management. Here, we review biomaterials developed to modulate the immune system, with an emphasis on innate immunity. We specifically highlight the recent implementation of functionalized surfaces for immunomodulation, including metal ion releasing coatings, stimuli-responsive polymeric coatings, and interleukin releasing surfaces. We also describe immunomodulatory nanoparticles, including lipid-based nanoparticles, biomimetic nanoparticles, and inorganic nanocarriers. Lastly, we explore immunomodulatory hydrogels used primarily for the treatment of wound infections. These approaches offer new strategies for treating bacterial infections and enhancing existing antimicrobial approaches, all while avoiding complications associated with antimicrobial resistance.